The Effect of Technological Innovation on Sustainability and Industry 4.0 Implementation: An Empirical Analysis of Indonesian Small and Medium-Sized Businesses - Zainul Wasik; Dedy Iswanto; Muchammad Saifuddin (Journal of Managerial Sciences and Studies, 2024)
Small and medium-sized businesses, or SMEs, are the foundation of the majority of economies in the world. Small and medium-sized enterprises (SMEs) will find it extremely difficult to improve their performance and hard to meet their sustainability objectives in the absence of qualified technological innovation. Hence, Industry 4.0 (I4.0), the next technology frontier, should be embraced by small firms. This study's primary goal is to comprehend the connection between sustainability objectives and the adoption of Industry 4.0 (I-4.0) technologies. It also examines how innovative features facilitate the adoption of I-4.0 by small enterprises. In order to address the research inquiries and scrutinize the intricate data, AMOS software was used to conduct a structural equation model in this study. The findings showed that the adoption of I-4.0 and sustainability objectives are positively and significantly impacted by the features of technological innovation. With the exception of observability, effective I-4.0 implementation mediates the relationship between innovation traits and sustainability goals. According to the research's conclusions, SMEs should create an effective I-4.0, put it into practice, and cultivate innovative traits in order to meet sustainable objectives.